1989
DOI: 10.1002/ana.410250303
|View full text |Cite
|
Sign up to set email alerts
|

Neurological disease associated with antiphospholipid antibodies

Abstract: The Hemostasis and Thrombosis Laboratory at the Oregon Health Sciences University identified 80 patients with significantly elevated anticardiolipin antibody (ACLA) levels. We reviewed all of their available medical records and found that 25 of these patients had associated neurological symptoms or disorders. These symptoms and disorders could be grouped into four distinct clinical patterns comprising encephalopathy, multiple cerebral infarctions, migraine-like headaches, and visual abnormalities including ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1
4

Year Published

1989
1989
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(105 citation statements)
references
References 44 publications
4
96
1
4
Order By: Relevance
“…18 These antibodies have been associated with systemic thrombotic problems including major arterial occlusions, deep-vein thrombosis, and pulmonary hypertension, as well as with thrombocytopenia and recurrent fetal abortion. 21 " 23 Asherson et al 24 reported a relation between CVD and antiphospholipid antibodies in patients with SLE and related disorders. Multiple episodes of cerebral infarction are common in patients with antiphospholipid antibodies, and some patients develop multi-infarct dementia during the course of their illness.…”
Section: Discussionmentioning
confidence: 99%
“…18 These antibodies have been associated with systemic thrombotic problems including major arterial occlusions, deep-vein thrombosis, and pulmonary hypertension, as well as with thrombocytopenia and recurrent fetal abortion. 21 " 23 Asherson et al 24 reported a relation between CVD and antiphospholipid antibodies in patients with SLE and related disorders. Multiple episodes of cerebral infarction are common in patients with antiphospholipid antibodies, and some patients develop multi-infarct dementia during the course of their illness.…”
Section: Discussionmentioning
confidence: 99%
“…Antiphospholipid antibodies of the immunotested negatively for anticardiolipin antibodies (n Å 37), globulin (Ig) G isotype show the strongest association but were present in 16.7% of those positive for anticard-with symptomatic disease. [1][2][3][4][5][6][7][8][9][10] iolipin (n Å 36) (P Å .01). In conclusion, anticardiolipin Anticardiolipin antibodies have been detected in a antibodies are frequently found in patients with chronic variety of infectious diseases, particularly of viral orihepatitis C and in these patients they may be implicated gin, such as human immunodeficiency virus infection, in the occurrence of thrombosis and in the development of thrombocytopenia.…”
Section: Titis C Patients the Presence Of Thrombocytopenia Portalmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] The idea of a possible six patients, and the second determination was positive implication of antiphospholipid antibodies in thromboin three of them.…”
Section: Titis C Patients the Presence Of Thrombocytopenia Portalmentioning
confidence: 99%
“…The pathophysiology of spinal cord damage in these patients is unknown, but ischemia or direct interaction of aPL with CNS phospholipids has been suggested (43). Several studies suggest an association between aPL and Guillain-Barré syndrome, seizures, chorea (44) and migraine headaches (45).…”
Section: Neurological Complicationsmentioning
confidence: 99%